Pediatric CNS Tumors - Gupta, Nalin; Banerjee, Anuradha; Haas-Kogan, Daphne A. (Pediatric Oncology,, 2017)
Pediatric CNS Tumors is a detailed review of childhood brain tumors that offers a biologically based perspective on their management. For each tumor type, epidemiology, pathological features, clinical presentation, diagnosis, and treatment are discussed. Particular emphasis is placed on the provision of treatment algorithms that reflect current best practice, and controversies and therapeutic agents under development are also addressed. The closing chapters consider many of the diagnostic and treatment modalities common to all tumors, with special attention to experimental and emerging techniques. This third edition of the book has been thoroughly revised and updated to take into account the latest advances in knowledge and treatment.